A contribuição socioambiental e econômica da Associação de Catadores Recicla Pampa ao município de Caçapava do Sul - RS - (:unkn) unknown (Universidade Federal do Pampa, 2020)
Daily, in Brazil, high amounts of solid residues are generated, in which are constituted in good part of disposable materials that could be reutilized or recycled, instead of being disposed in inappropriate areas, being the cause of many general liabilities. Reinsuring that submitting this waste to the sanitary landfill, an environmental adequate local to the disposal of domestic waste, reduce the lifetime of it, especially in reason of the economic potential that those products possess. In this background, new actors arise, playing an important role on the collection and recycling process: the recyclable material collectors, that, although submitting important socioeconomic and environmental contribution are still facing many difficulties and prejudice regarding the work activity. Looking into it, this present study has as objective present the actual situation of a association of collectors of recycling material on the city of Caçapava do Sul (RS), such as their municipal contribution in order to give the opportunity of recognition in front of the community and stimulating the environmental conciseness on the local residents. With the purpose of obtaining the necessary data, a field study was made, characterizing the research as descriptive. With the execution of this work it was possible to contribute significantly to the recognition and valuation of the recycling material collectors working class in Caçapava do Sul, in special to the professionals of the Association Recicla Pampa.
Keywords: Resíduos sólidos; Catadores de materiais recicláveis; Reciclagem; Solid waste; Recycled material scavengers; Recycling; CNPQ::CIENCIAS EXATAS E DA TERRA